INFLUENCE OF IODINE DEFICIENCY CONDITIONS IN WOMEN ON PREGNANCY AND CHILD DEVELOPMENT - M. S. Shodieva (International Engineering Journal For Research & Development, 2022)
The article discusses the influence of iodine deficiency conditions on pregnant women and children. The authors found that iodine deficiency in pregnant women is accompanied by an increased frequency of miscarriage -23.2% and anemia-37.1%,